COGNITIVE LOAD REDUCTION STRATEGY IN LEARNING STOICHIOMETRY FOR 3T STUDENTS: AN APPROACH TO OVERCOMING COGNITIVE LOAD IN CHEMISTRY NUMERATION - Damayanti, Yosephine Debbie; Putri, Rinda Angghita (Universitas Negeri Semarang, 2025)
This study aims to analyze the effectiveness of cognitive load reduction strategies in improving 3T students' understanding of the concept of stoichiometry. Students from 3T areas often have difficulty in understanding chemical concepts due to limited access to quality learning resources and challenges in numeracy. Therefore, this study applies a cognitive load reduction strategy that includes material segmentation, scaffolding, concept visualization, and the use of analogies and real contexts in stoichiometry learning. The research method used is a quasi-experiment with a pretest-posttest control group design. The subjects of the study consisted of 3T students who were divided into experimental groups and control groups. Data were collected through a stoichiometry understanding test, a cognitive load questionnaire, and in-depth interviews. The results of the analysis showed that the experimental group experienced a significant increase in posttest scores compared to the control group. In addition, students in the experimental group showed a higher level of understanding retention and a reduction in misconceptions after the implementation of the cognitive load reduction strategy. This study provides evidence that the cognitive load reduction strategy can improve the effectiveness of stoichiometry learning by reducing students' cognitive load. The implications of this study suggest that this approach can be applied more widely in chemistry teaching to improve students' conceptual understanding and numeracy skills. Thus, the results of this study can be the basis for the development of more innovative and adaptive teaching methods for students with diverse educational backgrounds.